Continuous, objective measurement of physical activity during chemotherapy for breast cancer: the Activity in Treatment pilot study. Issue 4 (29th May 2019) - Nelson, Sandahl H; Weiner, Lauren S; Natarajan, Loki; Parker, Barbara A; Patterson, Ruth E; Hartman, Sheri J
Abstract : Women who were treated with chemotherapy for breast cancer became less active throughout the first half of chemotherapy, but then activity leveled off and did not reduce more in the second half of chemotherapy. Abstract: Despite many potential benefits of physical activity during and after breast cancer treatment, activity levels typically decline from pre- to posttreatment. Most previous research has relied on self-reported activity. The purpose of this study were to assess patterns of daily, to objectively measured physical activity throughout chemotherapy for breast cancer, and to identify predictors of physical activity patterns. Participants were given a Fitbit before starting chemotherapy and asked to wear it throughout chemotherapy. Restricted cubic splines assessed nonlinear patterns of Fitbit measured total physical activity (TPA) and moderate-to-vigorous physical activity (MVPA) throughout the duration of chemotherapy (mean = 17 weeks, standard deviation [ SD ] = 6.3). Mixed-effects regression models assessed the rate of physical activity decline. Regressions of subject-level random slope assessed predictors of the rate of physical activity decline on participant and cancer characteristics and self-reported physical and cognitive functioning. Participants ( n = 32) were on average 50 years old; the majority had stage II breast cancer. MVPA declined linearly at a mean rate of 1.4 min/day ( p = .002) for every 10% of chemotherapy completed, whereas TPA declined linearly at an average rate of 13.4 min/day ( p = .0007) for every 10% of chemotherapy completed, until around halfway through chemotherapy, when activity rates leveled off. HER+ receptor status was associated with a greater rate of MVPA decline, β = 13.3, p = .04. This novel study of objectively measured daily MVPA throughout chemotherapy showed that most reductions in activity occurred during the first half of a course of chemotherapy. Targeting this early period of chemotherapy may be important for preventing declines in activity levels throughout chemotherapy.